Transparent evaluation of scholarly communications - Quintana, Daniel; Heathers, James (Septentrio Conference Series, 2020)
The processes behind the evaluation of scholarly communications are mostly conducted behind closed doors, with only the final published output accessible to readers. The criteria used to decide which manuscripts are sent out for peer-review and ultimately accepted for publication are often vague and hard to interpret. Without access to peer-review reports and editorial comments, it is also unclear how published manuscripts have been assessed. In this conversation, we will discuss the benefits of transparent scholarly communication and the challenges of implementing fully-transparent processes. We will also cover the how social media and podcasts can be used to demystify the publication process by providing an open forum for discussing the myriad publication processes that are typically unwritten, such as rebutting reviewer comments. The recording of the live podcast episode is at https://youtu.be/1Xp3IXaq970.